ANALISIS FAKTOR PENYEBAB INVOLUNTARY DELISTING PERUSAHAAN DI INDONESIA - LAKHAYE, ARVIN (Jurnal Akuntansi AKUNESA, 2014)
This research aims to analyze the factors that cause to involuntary delisting companies in Indonesia. This research examines five independent variables, which include managerial ownership, size of independent commissioners, external auditor, debt to equity ratio, and return on equity ratio, whereas the dependent variable that used is involuntary delisting. The population that used in this research are companies which are listed on the Indonesia Stock Exchange 2007-2013. The sample used in this research are companies that fulfill criteria of purposive sampling, the final sample researched consists of 43 companies. Analysis techniques that used to test the hypothesis is the logistic regression analysis by using SPSS version 22, moreover also conducted a test overall fit model and goodness of fit test. Test result of overall fit model shows that with additional independent variables like managerial ownership, external auditor, size of independent commissioners, debt to equity ratio, and return on equity can fix the fit model. Based on goodness of fit test shows that the model is acceptable because it fit with its observation data.Keyword: Involuntary delisting , good corporate governance, financial performance.